Practical Immunodermatology - Gao, Xing-Hua; Chen, Hong-Duo (Springer Netherlands : Imprint: Springer, 2017)
This book discusses typical skin diseases from an immunological point of view, introducing the latest immunological techniques and practices. It begins with a brief overview of the human immune system, including the basic concepts and principles as well as the general symbols used in immunology. Part Two describes the human skin as an integral part of the immune system, explaining the immunological roles of major cellular and molecular composites in the skin. Part Three illustrates typical skin diseases that have immunological involvement (immunodermatological conditions). It describes 40 skin diseases, focusing on immunological causes, pathogenesis, pattern of reaction and treatment choices and responses. The final part discusses advanced immunodiagnostics and immunotherapy in dermatology, providing detailed descriptions of immune techniques for the diagnosis of skin diseases, their principles and background, indications, requirements for sampling, test protocols, interpretation of results and trouble shooting. This work offers insights into both the systemic immune system and the skin immune system, and integrates the information into discussions of clinical diseases, relevant immune techniques and immunological drugs. Presenting the latest advances in clinical immunology, it is an invaluable resource for dermatologists, residents and graduate students in dermatology.
Keywords: Medicine.; Immunology.; Dermatology.; Internal medicine.; elektronické knihy; electronic books